Initial Analysis of The Characteristics of Sweet Orange (Citrus Sinensis) Peel Essential Oils as an Alternative Surfactant in The Tertiary Oil Recovery Method - Arik Daniati; Novia Rita; Romal Ramadhan; Desi Purnama Sari (Testing Center for Oil and Gas LEMIGAS, 2023)
Surfactant flooding is one of the types of EOR that reduces the surface tension between two immiscible fluids. The essential oil of sweet orange peel (citrus sinensis) contains a methyl ester group found in the pectin of sweet orange peel, so it has the potential as a raw material for making Methyl Ester Sulfonate by transesterification and sulfonation processes using H2SO4 reactants. This research is focused on testing the MES characteristics of the essential oil of orange peel in the form of density, viscosity, pH, acid number, and compatibility tests. The results of testing the characteristics of the essential oil of sweet orange peel obtained a density of 0.9 g/cm3, a viscosity of 1.36 cP, a neutral pH of 7, and an acid number of 3.048%, so based on these characteristic values the MES of the essential oil of orange peel was included in the initial screening. Alternative MES. Based on the surfactant compatibility test with a concentration scenario of 0.1%, 0.3%, 0.5%, 0.7%, and 1% in brine with a salinity of 15,000 ppm, the best is the 0.1% surfactant scenario. However, all scenarios qualify for compatibility. Certain surfactant solutions are not clear or cloudy, but that does not mean they cannot be injected